Productivity and foreign ownership in the UK car industry - Rachel Griffith (Institute for Fiscal Studies (IFS), 1999)
Many sectors of the UK economy experienced rapid productivity growth over the 1980's. This coincided with an increase in the flow of inward investment. Studies using macro data have linked these two events. This paper investigates what has happened in one industry at the microeconomic level and asks whether foreign-owned establishments in the UK car industry more productive than domestic-owned ones. Production functions are estimated using a new panel data set at the plant level. The findings suggest that, while foreign-owned establishments have higher output and value-added per worker, these differences appear to be largely explained by different levels of factor usage. Foreign-owned firms invest more in physical capital and use more intermediate goods. They also pay their workers higher wages. Differences in levels of total factor productivity still exist but they are relatively small.
Keywords: D24; F21; L23; 330